Asia - Aspen-Baxter, Linda (New York : AV2 by Weigl, 2013)
Examines the location and resources, economy, history, and culture of Asia.
Includes index.
7.6
5-8
Keywords: Continents; Asia -- Juvenile literature; Asia; Asia; Asia